Checklist of trees in Crocker Range Park permanent research plot, Sabah, Malaysia - Rimi Repin; Luiza Majuakim; Monica Suleiman; Reuben Nilus; Handry Mujih; Geofarry Gunsalam (Institute for Tropical Biology and Conservation, 2012)
This paper presents a checklist of trees from six 0.25 ha permanent research plots in Crocker Range Park (CRP). A total of 73 tree families with 199 genera and 527 species were identified from the plots. Euphorbiaceae was the largest family, with 15 genera containing 52 species. The other dominant tree families in terms of species composition were Myrtaceae, Lauraceae, Meliaceae, Rubiaceae, Moraceae and Annonaceae. The timber tree family, Dipterocarpaceae, consisted of 19 species with Shorea being the species rich genus. There were 21 least dominant families that were respresented by only one species. At least 47 species are new records for CRP, while three species are new records for Sabah - Gonystylus nervosus, Sterculia rhynchophylla and Palaquium ferrugineum. Seventy tree species were found to be endemic to Borneo, and seven species could be Sabah endemics. The findings of this paper show that CRP is diverse is diverse and rich in terms of tree flora.